The Influence of Learning Discipline on Learning Achievement of Islamic Religious Education (Pengaruh Disiplin Belajar Terhadap Prestasi Belajar Pendidikan Agama Islam) - Nurul Aini; Syahrul Syahrul; Sitti Aisyah Mu'min (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This study aims to measure the effect of learning discipline on student achievement in Islamic Religious Education subjects. This type of research is quantitative with correlational techniques, data collected through questionnaires to 33 samples from class IV to class VI. Data analysis used descriptive and inferential statistics. The results showed that: 1) Student learning discipline in Islamic Religious Education subjects was included in the good category, obtaining 36.37%. This value exceeds the moderate category which gets 33.33%, while the very good category gets 30.30%. However, for the category of less or less, it does not show the value or frequency. 2) Student achievement in Islamic Religious Education subjects is included in the high category with a percentage reaching 78.8%, while other categories such as the high category reaching 21.2% and the medium, low and very low categories do not indicate any value or frequency. 3) There is a significant influence between learning discipline and student achievement in Islamic Religious Education subjects, this is evidenced by the value of tcount < ttable i.e. 1.138 < 1.69236. The contribution of student learning discipline only affects as much as 43%, while the remaining 57% comes from other factors not disclosed in this study.Keywords: Learning Discipline, Learning Achievement, Islamic Religious Education